(untitled) (Fiep Bulletin - online, 2019)
This study had as objective compares the level of practicing women’s of HIIT weigh loss in the three different hormonalphases: follicular. ovulatory and luteal. through weightings in a bioimpedance scale. It is a research bibliographical. descriptive.quantitative of semi-experimental stamp. The sample was composed by 15 women. with age group between 21 and 47 years.divided in two groups: 8 made contraceptive use and 7 didn’t do. The participants practiced sessions of HIIT frequently of at leastthree times the week during two hormonal cycles. The weightings took place for two months always in the beginning of thetraining sessions. the first. Monday and third weighting happened in the phases follicular. ovulatory and luteal respectively. To theend of the sessions of HIIT they answered the scale of subjective perception of effort of OMNI-RES (GEARHART et al. 2009). Thecollected data were made available in a spreadsheet of Excel for Windows and inserted in a statistical program where was wereanalyzed the normality. frequency. measures of central tendency and dispersion. also tested by the association of the variableswith the correlation of Pearson with pvalue<0.05. It was noticed that the weight in the beginning of the weightings and in the end ofthe weightings it was directly proportional. in other words. he/she stayed. Already the percentile of thin mass was shown inverselyproportional to the weight. having expressive increase of thin mass with the practice of sessions of HIIT.